Real-time Analog Pixel-to-pixel Dynamic Frame Differencing with Memristive Sensing Circuits - Olga Krestinskaya; Alex Pappachen James (My University, 2018)
In this paper, we propose an analog pixel differencing circuit for differentiating pixels between frames directly from CMOS pixels. The analog information processing at the sensor is a topic of growing appeal to develop edge‑AI devices. The proposed circuit is integrated into pixel‑parallel and pixel‑column architectures. The system is designed using TSMC 180 nm CMOS technology. The power dissipation of the circuit is 96.64 mW, and the on‑chip area is 531.66 µm². The architectures are evaluated in a moving object detection application.
Keywords: analog pixel differencing; memristive sensing circuit; pixel-parallel architecture; dynamic frame differencing; edge AI; TSMC 180 nm CMOS; power dissipation; on-chip area